An Interview with Dr. Roger Lee - Vietgen, Peter; Black, Joanna (The Canadian Art Teacher / Enseigner les arts au Canada, 2023)
Never before has the change from face-to-face teaching been so challenged as during COVID-19. In order to understand the present, we turn to the past. The interviewers interviewed Dr. Roger Lee about his first online Art Education program in Canada to shed light on our new day-to-day reality for many of turning to virtual teaching and learning on online platforms.